CASE STUDY ON MODERNIZATION TRANSFORMATION AND PERFORMANCE IMPROVEMENT OF PAPER PRINTING INDUSTRY - Jung Chen, Li; Chiuan Lin , Chin (International Journal of Application on Economics and Business, 2025)
After the COVID-19 pandemic, global economic growth slowed down in 2022. Although Taiwan was affected, its competitiveness remained strong. According to data from the Ministry of Economic Affairs, there are more than 1.63 million small and medium-sized enterprises in Taiwan, accounting for more than 98% of all enterprises, a record high; the number of employees in small and medium-sized enterprises is 9.132 million, accounting for 80% of the national employment, and its sales exceed 28 trillion NTD, accounting for more than 50%, and the export volume is 3.6 trillion NTD, with an annual growth rate of more than 7%, showing the importance of small and medium-sized enterprises in Taiwan's economic development. Since 2021, many industries have been crying out for a shortage of workers. Taiwan's low birth rate is severe, and the COVID-19 epidemic has also led to a serious shortage of workers in various industries. It is a common problem for traditional industries to "not find people". Taiwan's economic growth momentum is mainly concentrated in the manufacturing industry, among which "semiconductors" and "information electronics" are the main foundations. The country's tax revenue mostly relies on "export trade", and the manufacturing industry naturally becomes an important source of financial income. Today, traditional industries are facing high costs of land, labor, water and electricity, and raw materials, which have resulted in insufficient growth momentum and stagnation. Coupled with the reciprocal tariffs implemented by the United States in 2025, Taiwan's traditional industries are facing even more severe challenges to survival. How traditional industries should apply modern technology to transformation is the most important issue at present. How to find opportunities through R&D innovation, and then promote corporate culture transformation, technological innovation and guide new smart skills to apply sustainable manufacturing (also known as green production). Promoting the integration of traditional industries with innovative industries, reducing negative impacts on the environment and carbon emissions, and saving energy are currently important issues.